2016
DOI: 10.1159/000446544
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Diagnosis of Primary Autoimmune Hypophysitis in a Prospective Single-Center Experience

Abstract: Background: Autoimmune hypophysitis is a rare disease with a natural progression that is not well known. Aim: To collect representative data on clinical features of autoimmune hypophysitis and better characterize the disease. Patients and Methods: A prospective single-center study was designed. Autoimmune hypophysitis-affected patients evaluated from 2011 at our tertiary care Pituitary Unit were enrolled. After ruling out other pituitary masses and secondary causes of hypophysitis, autoimmune hypophysitis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 33 publications
2
37
1
4
Order By: Relevance
“…On some occasions, in cases of primary hormonal deficiency (such as primary hypothyroidism, primary hypoadrenalism and primary hypogonadism), a compensatory pituitary hypertrophy occurs (20). At least, also in hypophysitis, which represents an emerging and more frequently diagnosed disease (34), pituitary hyperplasia could evolve in empty sella, as last stage of disease, as suggested by the presence of antipituitary antibodies in around 6% of PES cases (35).…”
Section: Pituitary Factorsmentioning
confidence: 99%
“…On some occasions, in cases of primary hormonal deficiency (such as primary hypothyroidism, primary hypoadrenalism and primary hypogonadism), a compensatory pituitary hypertrophy occurs (20). At least, also in hypophysitis, which represents an emerging and more frequently diagnosed disease (34), pituitary hyperplasia could evolve in empty sella, as last stage of disease, as suggested by the presence of antipituitary antibodies in around 6% of PES cases (35).…”
Section: Pituitary Factorsmentioning
confidence: 99%
“…The recognition of infectious/inflammatory diseases as the important causes of hypopituitarism has increased in the recent years [23]. Pituitary abscesses and the infection of the central nervous system of various etiologies, tuberculosis-TBC, and other bacterial, viral, and fungal infections can affect hypothalamo/pituitary axis and disrupt its function [24, 25].…”
Section: Introductionmentioning
confidence: 99%
“…According to clinical and neuroradiological findings, hypophysitis can involve the anterior pituitary gland, infundibulum, posterior lobe (infundibuloneurohypophysitis) or the entire pituitary gland (panhypophysitis) (13). Infundibuloneurohypophysitis is related to the etiological diagnosis of anterior hypopituitarism, particularly GH deficit, and secondary hypogonadism and DI (14). In other studies, it was reported that primary hypophysitis was usually seen in the anterior lobe of hypophysitis (15), and symptoms due to anterior pituitary hormone deficiency were the highest (16).…”
Section: Discussionmentioning
confidence: 99%